2014
DOI: 10.1111/1471-0528.12875
|View full text |Cite
|
Sign up to set email alerts
|

Interest in multipurpose prevention of HIV and pregnancy: perspectives of women, men, health professionals and community stakeholders in two vaginal gel studies in southern Africa

Abstract: Objective The pipeline of vaginal microbicides for HIV prevention has expanded to include products for multipurpose prevention, but the interests of potential users and those advising on use have not been sufficiently investigated. Rather, assumptions about interest in multipurpose prevention technologies (MPTs) are inferred from what is known about acceptability and use of microbicides or contraceptives.Design and setting This paper presents data on concerns and preferences for multipurpose prevention of HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…As a result, a raft of new ring designsstill largely based around silicone elastomer, EVA and TPU materials (see Section 2.3)has emerged aimed at overcoming this permeation barrier, including segmented matrix, multi-core, segmented reservoir, rod/tablet insert, core-matrix and pod insert rings ( Figure 2). A major impetus for continued innovation in ring design has been the growing interest in combination microbicide [45] and multipurpose prevention technology products [46][47][48][49] (see Section 2.8), for which release characteristics need to be individually tailored for each drug molecule. The release mechanisms that govern these new designs are discussed in Section 2.4.…”
Section: Types Of Vaginal Rings For Microbicide Deliverymentioning
confidence: 99%
“…As a result, a raft of new ring designsstill largely based around silicone elastomer, EVA and TPU materials (see Section 2.3)has emerged aimed at overcoming this permeation barrier, including segmented matrix, multi-core, segmented reservoir, rod/tablet insert, core-matrix and pod insert rings ( Figure 2). A major impetus for continued innovation in ring design has been the growing interest in combination microbicide [45] and multipurpose prevention technology products [46][47][48][49] (see Section 2.8), for which release characteristics need to be individually tailored for each drug molecule. The release mechanisms that govern these new designs are discussed in Section 2.4.…”
Section: Types Of Vaginal Rings For Microbicide Deliverymentioning
confidence: 99%
“…Interviews with African women participating in HIV prevention trials demonstrated substantial interest in using multipurpose products [90]. Ideally, multiple approaches to delivering PrEP will be efficacious and manufactured for public use, including topical, oral and injectable formulations, so that prevention options may be individualized based on each person’s sexual behaviors, patterns of exposure, and personal preferences.…”
Section: Pre-exposure Prophylaxis (Prep)mentioning
confidence: 99%
“…An MPT that combines HIV and pregnancy prevention could offer several advantages over two single‐indication products: it may improve motivation to use and acceptability by bundling a more common outcome (pregnancy) with a rarer and more stigmatized one (HIV), it simplifies use with potential adherence optimization, and it may also decrease burden on local health systems . Research so far has shown that African women overwhelmingly favor an MPT . However, well‐known challenges associated with condom, an existing MPT, (e.g.…”
Section: Introductionmentioning
confidence: 99%